The Effect of Phosphorus on Relative Rates of Mineralisation of Nitrogen in Different Organic Manures - Moghe, V. B.; Sinha, S. B. (Journal of Soil and Water Conservation, 2022)
Microbiological activity plays a prominent part in building up and maintaining the fertility of soil at a higher level. In fact, decomposition of organic matter in the soil is mostly a microbiological process accom- panied by important changes in carbon and nitrogen which are intimately related to soil fertility. Organic nitrogen is oxidized in different stages by distinct microbial processess.It is well known that microbial cells contain highest amounts of phosphorus in their cell constituents, which indicates that suffciency or deficiency of the same in the soil would affect the growth and activity of different soil micro-organisms. Stimulation of decomposition of organic matter in soil by addition of phosphates had been observed Increase in by Waksman and Starkely (II). nitrification in various degrees in soil due to addition of phosphates was noted by Peterson and Scott. (5), Brown and Gowda (l) Fraps and Starges (2), Fulmer (3) and Whiting and Scoonover (9).